CHRONIC RADIATION-INDUCED BRAIN CHANGES AFTER IRRADIATION OF ENDOCRANIUM - Mudrić, Maja B; Boban, Jasmina (Medicinski podmladak, 2019)
Abstract Introduction: Irradiation is an essential part of therapy for brain malignant tumors that can prolong life for terminally ill patients. However, it causes radiation-induced complications, divided into acute, early delayed and late, that all vary on the applied radiation dose. Material and methods: This retrospective study included 41 patients of both sex. Study was performed in the Center for imaging diagnostics of Oncology Institute of Vojvodina, using the database BIRPIS. MRI scans consisted of: T2 axial, FLAIR axial, T1 precontrast axial, SWI and T1 axial 3D MP-RAGE postcontrast tomograms. Evaluated changes were: cavernoma, angioma, gliosis, aneurysm, haemorrhage, hydrocephalus and other. For analysis we used methods of descriptive statistics. Results: The most common change in this study was gliosis (92.68%), followed by cavernoma (53.65%), hydrocephalus (26.83%) and angioma (21.95%). Haemorrhage and aneurysm were not found. Dilated perivascular spaces were found in 80% of the patients; this finding has not yet been described in this group of patients. Conclusion: Late radiation-induced changes supposedly develop as a result of interaction of vascular and parenchymal dysfunction. Given the high frequency of dilated perivascular spaces observed in treated white matter, neuroinflammation could be another contributor to these changes. Keywords: magnetic resonance imaging; brain; radiation injuries;